Shape-dependent thermo-plasmonic effect of nanoporous gold at the nanoscale for ultrasensitive heat-mediated remote actuation. Issue 34 (16th August 2018) - Yang, Zhe; Han, Xuemei; Lee, Hiang Kwee; Phan-Quang, Gia Chuong; Koh, Charlynn Sher Lin; Lay, Chee Leng; Lee, Yih Hong; Miao, Yue-E; Liu, Tianxi; Phang, In Yee; Ling, Xing Yi
Abstract : Nanoscale shaping of NPG's thermo-plasmonic effect is investigated to optimize localized light-to-heat conversion and its application in ultrasensitive heat-mediated actuation. Abstract : Nanoporous gold (NPG) promises efficient light-to-heat transformation, yet suffers limited photothermal conversion efficiency owing to the difficulty in controlling its morphology for the direct modulation of thermo-plasmonic properties. Herein, we showcase a series of shape-controlled NPG nanoparticles with distinct bowl- (NPG-B), tube- (NPG-T) and plate-like (NPG-P) structures for quantitative temperature regulation up to 140 °C in <1 s using laser irradiation. Notably, NPG-B exhibits the highest photothermal efficiency of 68%, which is >12 and 39 percentage points better than those of other NPG shapes (NPG-T, 56%; NPG-P, 49%) and Au nanoparticles (29%), respectively. We attribute NPG-B's superior photothermal performance to its >13% enhanced light absorption cross-section compared to other Au nanostructures. We further realize an ultrasensitive heat-mediated light-to-mechanical "kill switch" by integrating NPG-B with a heat-responsive shape-memory polymer (SMP/NPG-B). This SMP/NPG-B hybrid is analogous to a photo-triggered mechanical arm, and can be activated swiftly in <4 s simply by remote laser irradiation. Achieving remotely-activated "kill switch" is critical in case of emergencies such as gas leaks, where physical access is usually prohibited or dangerous. Our work offers valuable insights into the structural design of NPG for optimal light-to-heat conversion, and creates opportunities to formulate next-generation smart materials for on-demand and multi-directional responsiveness.